2022
DOI: 10.1371/journal.pone.0277458
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics confirms the association between plasma branched chain amino acids and residual feed intake in beef heifers

Abstract: This study explored plasma biomarkers and metabolic pathways underlying feed efficiency measured as residual feed intake (RFI) in Charolais heifers. A total of 48 RFI extreme individuals (High-RFI, n = 24; Low-RFI, n = 24) were selected from a population of 142 heifers for classical plasma metabolite and hormone quantification and plasma metabolomic profiling through untargeted LC-MS. Most efficient heifers (Low-RFI) had greater (P = 0.03) plasma concentrations of IGF-1 and tended to have (P = 0.06) a lower ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
(78 reference statements)
1
9
0
Order By: Relevance
“…For instance, Elolimy et al [10], observed a connection between RFI and protein turnover and transport mechanisms in rumen epithelium of beef cattle. Our recent study by Taiwo et al [11] and those of others [1214] have further illuminated the link between RFI and amino acid metabolism in beef cattle. The results of these studies invariably highlight amino acid metabolism as one of the pathways associated with RFI phenotype in beef cattle, implying significant disparities in nitrogen utilization efficiency among beef cattle based on RFI variations.…”
Section: Introductionmentioning
confidence: 75%
“…For instance, Elolimy et al [10], observed a connection between RFI and protein turnover and transport mechanisms in rumen epithelium of beef cattle. Our recent study by Taiwo et al [11] and those of others [1214] have further illuminated the link between RFI and amino acid metabolism in beef cattle. The results of these studies invariably highlight amino acid metabolism as one of the pathways associated with RFI phenotype in beef cattle, implying significant disparities in nitrogen utilization efficiency among beef cattle based on RFI variations.…”
Section: Introductionmentioning
confidence: 75%
“…Group B-Restricted (0-70 days) www.nature.com/scientificreports/ branched-chain amino acids, decreased in efficient compared to inefficient RFI heifers 15 . Likewise, studies in pigs have also linked plasma α-aminoadipic acid levels and the lysine degradation pathway to the RFI phenotype 26 .…”
Section: Pearson Correlation Coefficient P Valuementioning
confidence: 99%
“…The plasma concentration of IGF-1 has been shown to correlate with RFI in various cattle studies 15,36 . However, diet-dependent relationships were highlighted in a review of the literature 4 , with a negative relationship, such as the one found in the present study, consistently observed only with low-concentrate and low-energy diets.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Dietary protein optimization based on metabolomic insights can lead to precise feeding for sustainable livestock production as varying dietary protein levels can lead to changes in metabolite profiles and metabolic pathways. It is established that dietary protein levels have an influence on amino-acid metabolism leading to changes in the concentrations of blood-circulating amino acids and related metabolic pathways in cattle [ 15 ]. Keeping in mind the intertwined metabolism of protein with energy, we assumed that changes in dietary protein contents may cause alterations in the concentrations of those metabolites that are involved in energy production, storage, and utilization.…”
Section: Introductionmentioning
confidence: 99%